1995
DOI: 10.1111/j.1365-2222.1995.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to two major allergens (Cry j I and Cry j II) in patients with Japanese cedar (Cryptomeria japonica) pollinosis

Abstract: Cry j II is an as important a major allergen as Cry j I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 7 publications
(5 reference statements)
2
49
0
Order By: Relevance
“…It has been reported that patients with Japanese cedar pollinosis exhibit a high titer allergen-specific IgE response (38). Allergenspecific IgE antibodies have been shown to play a major biological role for the induction of pollen-associated allergic responses (38, 39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with Japanese cedar pollinosis exhibit a high titer allergen-specific IgE response (38). Allergenspecific IgE antibodies have been shown to play a major biological role for the induction of pollen-associated allergic responses (38, 39).…”
Section: Discussionmentioning
confidence: 99%
“…Two major allergenic proteins, Cry j 1 and Cry j 2, have been isolated [1, 2]and both are thought to be important in the immunopathology of Japanese cedar pollinosis, since IgE specific to Cry j 1 was detected in up to 95% of the patients, while that to Cry j 2 in about 70% [2, 3, 4, 5]. Determination of primary structures of the Cry j 1 [6]and Cry j 2 [3, 7]was followed by the identification of multiple T–cell epitopes in both sequences [8, 9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The following allergens have been characterized in this source: Cry j 1, a 45-50 kDa protein, a pectate lyase, is considered a major allergen (Yasueda et al 1983;Taniai et al 1988;Griffith et al 1993;Sone et al 1994;Taniguchi et al 1995;Hashimoto et al 1995; (Ibrahim et al 2010b), and Cry j LTP, a Lipid Transfer Protein (Ibrahim et al 2010c). Moreover, a number of other antigenic proteins have been isolated but not characterized, including proteins of 7, 15 and 20 kDa (Matsumura et al 2006).…”
Section: Japanese Cedar (Cryptomeria Japonica Synonym: Cupressus Japmentioning
confidence: 99%